2019
DOI: 10.1186/s13023-019-1112-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac characteristics and natural progression in Taiwanese patients with mucopolysaccharidosis III

Abstract: Background Mucopolysaccharidosis type III (MPS III), or Sanfilippo syndrome, is caused by a deficiency in one of the four enzymes involved in the lysosomal degradation of heparan sulfate. Cardiac abnormalities have been observed in patients with all types of MPS except MPS IX, however few studies have focused on cardiac alterations in patients with MPS III. Methods We reviewed medical records, echocardiograms, and electrocardiograms of 26 Taiwanese patients with MPS III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…The presence of diastolic dysfunction was indicated by a reversed E/A ratio (E/A ratio < 1). The severity of valvular stenosis and regurgitation was evaluated and graded as follows: 0 (none), 1 (mild), 2 (moderate), and 3 (severe), according to the European Society of Cardiology guidelines [ 37 40 ]: mild aortic stenosis (AS) = a valve area > 1.5 cm 2 and a mean gradient < 30 mmHg; moderate AS = a valve area of 1.0–1.5 cm 2 and a mean gradient of 30–50 mmHg; severe AS = a valve area < 1.0 cm 2 and a mean gradient > 50 mmHg; mild mitral stenosis (MS) = a valve area > 1.5 cm 2 and a mean gradient < 5 mmHg; moderate MS = a valve area between 1.0–1.5 cm 2 and a mean gradient between 5–10 mmHg; and severe MS = a valve area < 1.0 cm 2 and a mean gradient > 10 mmHg. Because of the high frequency of physiological tricuspid regurgitation in the general population, we did not regard tricuspid regurgitation as a pathological finding in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of diastolic dysfunction was indicated by a reversed E/A ratio (E/A ratio < 1). The severity of valvular stenosis and regurgitation was evaluated and graded as follows: 0 (none), 1 (mild), 2 (moderate), and 3 (severe), according to the European Society of Cardiology guidelines [ 37 40 ]: mild aortic stenosis (AS) = a valve area > 1.5 cm 2 and a mean gradient < 30 mmHg; moderate AS = a valve area of 1.0–1.5 cm 2 and a mean gradient of 30–50 mmHg; severe AS = a valve area < 1.0 cm 2 and a mean gradient > 50 mmHg; mild mitral stenosis (MS) = a valve area > 1.5 cm 2 and a mean gradient < 5 mmHg; moderate MS = a valve area between 1.0–1.5 cm 2 and a mean gradient between 5–10 mmHg; and severe MS = a valve area < 1.0 cm 2 and a mean gradient > 10 mmHg. Because of the high frequency of physiological tricuspid regurgitation in the general population, we did not regard tricuspid regurgitation as a pathological finding in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The major storage products of MPS III and MPS IV are heparan sulfate and keratan sulfate, respectively. Therefore, cardiac lesions may be less prominent in patients with MPS III and IV than in those with MPS I, II, and VI [14,15,41].…”
Section: Discussionmentioning
confidence: 99%
“…Existence of diastolic dysfunction was indicated by a reversed E/A ratio (E/A ratio <1). The severity of valvular stenosis and regurgitation was assessed and graded as follows: 0 (none), 1 (mild), 2 (moderate), and 3 (severe), based on the European Society of Cardiology guidelines [12][13][14][15]35,36]: mild aortic stenosis (AS) = a valve area > 1.5 cm 2 and a mean gradient < 30 mmHg; moderate AS = a valve area of 1.0-1.5 cm 2 and a mean gradient of 30-50 mmHg; severe AS = a valve area < 1.0 cm 2 and a mean gradient > 50 mmHg; mild mitral stenosis (MS) = a valve area > 1.5 cm 2 and a mean gradient < 5 mmHg; moderate MS = a valve area between 1.0-1.5 cm 2 and a mean gradient between 5-10 mmHg; and severe MS = a valve area < 1.0 cm 2 and a mean gradient >10 mmHg. Because the frequency of physiological tricuspid regurgitation is high in the general population, we did not include tricuspid regurgitation as a pathological finding in this study.…”
Section: Conventional Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic root dilatation is frequently observed in animal models of MPS I, leading to the effacement of the sinotubular ridge [ 8 ]. Some studies have reported that aortic root dilatation may appear in various types of MPS patients, especially in those with MPS IVA [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%